The role of supply chains for the sustainability transformation of global food systems: a large-scale, systematic review of food cold chains - Trotter, Philipp A.; Becker, Tristan; Renaldi, Renaldi; Wang, Xinfang; Khosla, Radhika; Walther, Grit (Wiley, 2023)
Global food systems need an urgent transformation to be compatible with sustainable development. While much of the recent academic discussion has focused on food production and consumption, food supply chains have received considerably less attention. Here, we conduct a large-scale, systematic literature review of 48,014 academic articles to assess the links between the food cold chain literature and sustainable development. We find a multitude of deep links between food cooling and the Sustainable Development Goals (SDGs), but also identify underexplored areas of sustainable food cooling research regarding its (1) goals, (2) analytical depth, and (3) context specificity: There is a limited understanding how several relevant synergies between SDGs can be captured, how to best design sustainable food cold chains across multiple value chain stages, and how to scale sustainable cold chains in low-income and lower-middle-income country contexts. We recommend to explicitly consider the salient interconnections between SDGs, increase the analytical depth by deploying more system-level approaches across entire value chains, and focus on localized solutions in contexts where food supply chains are most underdeveloped.
Keywords: cold chains; food supply chains; Great Food Transformation; industrial ecology; sustainability transitions; sustainable food systems